PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, PERTUMBUHAN LABA, PROFITABILITAS, DAN LIKUIDITAS TERHADAP KUALITAS LABA - Nita Happi Amalia, 12.05.52.0177; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of capital structure, company size, profit growth, profitability, and liquidity influence on the quality of earnings. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2012 to 2014. The sample was determined by purposive sampling method, to obtain a sample of 148 manufacturing companies. The data used in this research is secondary data. Analysis of the data used is multiple regression analysis. The research proves that (1) the capital structure does not does not affect the quality of earnings, (2) the size of the company's positive and significant effect on the quality of earnings, (3) the profit growth had no effect on earnings quality, (4) profitability does not affect the quality, and (5) the liquidity does not affect the quality of earnings.Keywords: Capital Structure, Size of The Company, Profit Growth, Profitability, and Liquidity